Wandering corrections from PIV measurements of tornado-like vortices. Issue 189 (June 2019) - Ashton, Ryan; Refan, Maryam; Iungo, Giacomo Valerio; Hangan, Horia
Abstract: Wandering of tornado-like vortices consists in random oscillations of the vortex core from its time-averaged position, which complicates efforts to characterize vortex characteristics. A procedure is then necessary to retrieve characteristics of tornado-like vortices not affected by wandering smoothing effects. This study explores two procedures to correct wandering effects on Particle Image Velocimetry data obtained from a down-scaled model of the WindEEE Dome simulator. The first procedure re-centers the velocity data as a function of the instantaneous location of the vortex center. The second procedure treats the time-averaged vortex velocity field as the convolution of a bi-variate normal probability density function, which represents the distribution of vortex center locations over horizontal planes orthogonal to the vortex axis and the instantaneous tornado velocity field. Depending on swirl ratio and vortex height, wandering amplitude was generally from 5% to 9% of the updraft radius. The re-centering procedure was found to be more accurate than the deconvolution procedure. When applied to the turbulence statistics of the velocity field, the correction revealed that a higher level of turbulence at the center of low swirl tornadoes is a result of wandering. Also, the corrected shear stresses revealed a spiral pattern for cases of higher swirl. Wandering effects increases with reducing swirl ratio. For this experiment, swirl ratio is reduced from 0.96 down to 0.22 and errors on the vortex core radius as high as 50% and reduction of the maximum tangential velocity of 13% were observed. Highlights: For the first time, wandering effect of simulated tornado vortices are quantified. Re-centering procedure was found to be more accurate than the deconvolution method. Wandering amplitude was generally from 5% to 9% of the updraft radius. Wandering effects amplifies as the swirl ratio decreases. Wandering is responsible for a higher level of turbulence at the center of low swirl tornadoes.